A Comprehensive Review of the Hole-Drilling Method for Residual Stress Measurement: Principles, Challenges, and Modern Advancements - Jin, Xiaobei; Li, Zhanpeng; Liu, Genming (International Journal of Mechanical and Electrical Engineering, 2025)
The hole-drilling method is a widely used semi-destructive technique for determining residual stresses in engineering components. This paper provides a comprehensive review of the method’s evolution, fundamental principles, and modern advancements based on an analysis of key literature. The review begins by outlining the traditional application for measuring uniform surface stresses and traces its development into the incremental hole-drilling technique, which allows for the determination of residual stress variation with depth. Central to this evolution is the use of calibration coefficients, which correlate measured strain relaxation to the underlying stress state. This paper synthesizes the various analytical and computational approaches for deriving these coefficients, highlighting the pivotal role of the Finite Element Method (FEM) in modern practice. A significant portion of the review is dedicated to a critical examination of the method’s inherent challenges and sources of error, which include plasticity effects at high stress levels, the influence of component thickness (particularly in thin sheets), stress biaxiality, and discrepancies between ideal and real hole geometries. The literature reveals a consistent trend towards developing sophisticated correction procedures, often integrating FEM simulations with experimental data from both traditional strain gauges and advanced optical techniques like Digital Image Correlation (DIC). Persistent challenges include the lack of standardized procedures for thin components and highly plastic conditions. Future research directions point towards the development of integrated, multi-parameter correction models, further standardization, and the fusion of numerical simulations with full-field optical measurements to enhance the accuracy and expand the applicability of this vital measurement technique.